Integrating Educational Management Functions to Strengthen Link and Match Learning in Vocational Education - Ihsan Mustofa; Muhammad Idris; Subandi (Journal of Educational Management Research, 2026)
This study aims to analyze the implementation of educational management functions in strengthening the link and match approach between vocational education and the needs of business and industry. A qualitative library research method was employed using data collected from scholarly journal articles, books, government policy documents, regulations on vocational education, and other relevant studies. Data were gathered through documentation and literature review and analyzed using content analysis, including data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that the successful implementation of the link and match approach depends on the effective application of educational management functions. Planning is reflected in curriculum alignment with industry needs; organizing is realized through strengthening partnerships with business and industry; implementation is carried out through practice-based learning and the involvement of industry practitioners; while controlling is conducted through learning evaluation, tracer studies, and industry feedback. The study implies that strengthening educational management practices can improve the relevance of vocational education, enhance graduate competencies, and reduce the gap between educational outcomes and labor market demands.